A new species of skin-feeding caecilian and the first report of reproductive mode in Microcaecilia (amphibia: Gymnophiona: Siphonopidae). - Mark Wilkinson; Emma Sherratt; Fausto Starace; David J Gower (PLoS ONE, 2013)
A new species of siphonopid caecilian, Microcaecilia dermatophagasp. nov., is described based on nine specimens from French Guiana. The new species is the first new caecilian to be described from French Guiana for more than 150 years. It differs from all other Microcaecilia in having fewer secondary annular grooves and/or in lacking a transverse groove on the dorsum of the first collar. Observations of oviparity and of extended parental care in M. dermatophaga are the first reproductive mode data for any species of the genus. Microcaecilia dermatophaga is the third species, and represents the third genus, for which there has been direct observation of young animals feeding on the skin of their attending mother. The species is named for this maternal dermatophagy, which is hypothesised to be characteristic of the Siphonopidae.